COMUNICAÇÃO E ECONOMIA CRIATIVA: criação de um Hub de Inovação para Economia Criativa em São Luís (MA) - ABREU, Elber de Freitas (2023)
This present work reports on an applied research aimed at creating an Innovation Hub to strengthen the creative economy of São Luís-MA through community communication. The conception and development of this Innovation Hub relied on a methodology that included a bibliographic review on the study's topics, documentary research to gather secondary data related to the Creative Economy sector, surveys conducted with local stakeholders within the creative landscape, and the joint development with these city stakeholders of the final product using the agile Design Thinking method. As a result of this process, a strategic plan and a commitment letter of actions are presented to strengthen the creative economy in São Luís-MA as a minimum viable product, representing the first activity of the Innovation Hub. The research was significant due to the lack of consolidated data on the creative economy in São Luís, in addition to diagnosing the scenario to enable the creation of public policies. The Innovation Hub, born from this process, not only met the identified demand but also proved to be a communicational product designed to promote initiatives fostering the creative sector, also contributing to the United Nations' Sustainable Development Goals (SDGs),